1982
DOI: 10.1104/pp.70.4.1049
|View full text |Cite
|
Sign up to set email alerts
|

Salt Tolerance in Crop Plants Monitored by Chlorophyll Fluorescence In Vivo

Abstract: The potential of measurements of chlorophyll fluorescence in vivo to detect cellular responses to salinity and degrees of salt stress in leaves was investigated for three crop plants. Sugar beet (Beta vulgaris L.) (salt tolerant), sunflower (Heliandtws annuus L.) (moderately salt tolerant), and bean (Phaseohis Vulgaris L. cv Canadian Wonder) (salt intolerant) were grown in pots and watered with mineral nutrient solution containing 100 millimolar NaCI. The fast rise in variable chlorophyll fluorescence yield th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
3
3

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 17 publications
4
44
3
3
Order By: Relevance
“…The electron transport rate for intact chloroplasts or thylakoids was only slightly less than the control chloroplasts, in agreement with previous results for sunflower (22). Baker (2) found that high concentrations of NaCl or KCI inhibited electron transport when added to isolated spinach thylakoids.…”
Section: Discussionsupporting
confidence: 81%
“…The electron transport rate for intact chloroplasts or thylakoids was only slightly less than the control chloroplasts, in agreement with previous results for sunflower (22). Baker (2) found that high concentrations of NaCl or KCI inhibited electron transport when added to isolated spinach thylakoids.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies have shown that, in higher plants, salt stress inhibits PSII activity (Bongi & Loreto, 1989 ;Mishra et al, 1991 ;Masojidek & Hall, 1992 ;Belkhodja et al, 1994 ;Everard et al, 1994), whereas others have indicated that salt stress has no effect on PSII (Robinson et al, 1983 ;Brugnoli & Bjo$ rkman, 1992 ;Morales et al, 1992) or even increases PSII activity (Smillie & Nott, 1982). In cyanobacteria, the effect of salt stress of PSII has not been studied as intensively as in higher plants.…”
Section: mentioning
confidence: 99%
“…A medição da fluorescência da clorofila pode ser usada para revelar informações sobre os estádios de desenvolvimento de plantas (Bacarin & Mosquin 2002), para comparar genótipos (Portes & Magalhães, 1993;Campostrini & Maestri, 1998) e é usada, também, para investigar danos causados no aparato fotossintético, por diversas causas de estresses (Smille & Not, 1982;Strant & Oquist, 1988;Havaux et al, 1988;Torres Neto et al, 2002;El-Sheekh, 1993). Esta variável é uma significativa informação da eficiência fotoquímica do processo fotossintético (Torres Neto et al, 2002) Desta forma, as aferições da fluorescência e do potencial hídrico de espécies da Caatinga, que constituem objetivos deste trabalho, podem contribuir para o entendimento do processo evolutivo dessas plantas sob condições adversas, permitindo caracterizar as diferenças fisiológicas nas duas estações características da Região Nordeste, o período chuvoso e o período de estiagem.…”
Section: Introductionunclassified